THE AUTOMATED SYSTEM OF THE ANALYSIS AND ESTIMATION INVESTMENT PROJECTS OF THE AGRICULTURAL BUILDINGS - A. M. Abdulgalimov (Вестник Дагестанского государственного технического университета: Технические науки)
In work the information system, allowing to automate process of the analysis, an estimation and a choice of the investment project of agricultural building most favourable from the economic point of view on the basis of the comparative analysis of such indicators, as is offered: the modern (pure)discounted cost of the project,an index of profitableness (profitability) of real investments, internal norm of profitableness of real investments, profitability of actives of the project and a project time of recovery of outlay.